EFFECTS OF SUPPORTED SELF-CARE ON BLOOD PRESSURE AND CARDIOMETABOLIC PROFILE OF HYPERTENSIVE INDIVIDUALS: RANDOMIZED CLINICAL TRIAL - Moraes, Janaíne Chiara Oliveira; Bezerra, Simone Maria Muniz da Silva (Cogitare Enfermagem, 2022)
Objective: to verify the effects of supported self-care on the blood pressure and cardiometabolic profile of hypertensive individuals. Method: randomized clinical trial developed with 78 hypertensive patients monitored by the Family Health Strategy in the municipality of Cajazeiras - PB - Brazil. The intervention consisted of nursing consultations based on supported self-care. The control group followed up with the usual monitoring by the health team. For data collection, a sociodemographic and clinical questionnaire, blood tests, blood pressure and anthropometric measurements were used. Results: There was a reduction in weight, abdominal circumference, waist-to-hip ratio, and Body Mass Index in the intervention group, with significant improvement in blood pressure. No significant improvement was seen in the control group. Conclusion: supported self-care showed positive effects on the participants’ blood pressure and cardiometabolic profile, minimizing risk factors and configuring a methodology with promising potential when applied by nurses. REBEC - RBR-5m5qg8